Analyzing the role of family support, coping strategies and social support in improving the mental health of students: Evidence from post COVID-19 - Yang, Chunying; Gao, Hong; Li, Yuxiang; Wang, Enguo; Wang, Nina; Wang, Qinglei (Frontiers in Psychology, 2022)
Background The COVID-19 pandemic and the multifaceted response strategies to curb its spread both have devastating effects on mental and emotional health. Social distancing, and self-isolation have impacted the lives of students. These impacts need to be identified, studied, and handled to ensure the well-being of the individuals, particularly the students. Aim This study aims to analyze the role of coping strategies, family support, and social support in improving the mental health of the students by collecting evidence from post COVID-19. Methods Data was collected from deaf students studying in Chinese universities of Henan Province, China. A survey questionnaire was designed to collect data from 210 students. Descriptive statistics were calculated using SPSS 21 while hypothesis testing was carried out using Mplus 7. Results The results demonstrated that family support was strongly positively linked to mental health and predicted coping strategies. The direct relationship analysis showed that coping strategy strongly predicted mental health. Furthermore, coping strategies significantly mediated the relationship between family support and mental health. Additionally, the results highlighted that PSS significantly moderated the path of family support and coping strategies only. Conclusion Family support and coping strategies positively predicted mental health, whereas, family support was also found to be positively associated with coping strategies. Coping strategies mediated the positive association between family support and mental health. However, perceived family and other support only moderated the relationship between family support and coping strategies.